تطور الفكر السياسي عند جماعة "الإخوان المسلمين" في مصر‏‎ ‎قبل وبعد ثورة يناير‏‏2011م: دراسة تحليلية - بنا، إبراهيم عبد الله عبد الصادق (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The study aims at analyzing the development of the political thought of Ikwan al-Muslimin in Egypt and its vicissitudes during the period of pre-and post- Arab Spring Revolution . Deliberation on the definition of Ikwan al-Muslimin, its historical emergence, ideology, organization, aims and methodologies are covered in the beginning of the study. The political thought of Hasan al-Banna and Sayyid Qutb regarding the Islamic State as well as other related political concepts is also highlighted, followed by tracing the political and intellectual development of Ikwan al-Muslimin from the period of Hasan al-Banna until the movement gained its political power and leadership after the Revolution. The discussion on Ikwan al-Muslimin and its political and intellectual development during the period of Post Revolution is given due attention in the deliberation on the movement when it was given a chance to take power in Egypt through a series of popular elections, with Egyptians electing Islamist Mohamed Morsi, of The Freedom and Justice Party (believed to have strong links with the Muslim Brotherhood) to the presidency. Using the analytical, historical and comparative methods, the researcher concludes that under the political agenda of the party attempts have been made to manifest the idea of a civil based Islamic state, comprising of certain issues that have been abhorred previously by Hasan al-Banna himself, like multiple parties, citizenship, employment of women and democracy. These are altogether demonstrating various attempts by the movement to change its political thought in a way to suit the needs of the political reality. The agenda however, upon its implementation has been criticized by the opponents, created continuous crisis between the Ikwan al-Muslimin and its opponents and finally led to the political ouster of the movement from the political landscape. It was suggested that a comprehensive revision of the movement from all spectrums, including its political and intellectual dimensions, is of paramount importance, additionally, adopting a clear political direction and manifesto would ensure the survival of the movement and its continuous relevance in Egypt.